Electron dynamics in the core-excited CS2 molecule revealed through resonant inelastic x-ray scattering spectroscopy. (August 2015) - Marchenko, T; Carniato, S; Journel, L; Guillemin, R; Kawerk, E; Žitnik, M; Kavčič, M; Bučar, K; Bohinc, R; Petric, M; da Cruz, V Vaz; Gel'mukhanov, F; et al.
Synopsis: We present an experimental and theoretical study of resonant inelastic x-ray scattering (RIXS) in the CS2 molecule near the S 1s edge. We show that localization of the S 1s core-hole occurs in CS2 during the RIXS process due to the orientational dephasing of interference between the waves scattering on the two sulfur atoms. Strong evolution of the RIXS profile with the excitation energy far below the first absorption resonance reflects the onset of electron dynamics triggered by a coherent excitation of multiple electronic states.